2023
DOI: 10.1021/acs.jproteome.2c00790
|View full text |Cite
|
Sign up to set email alerts
|

CRISPRi-Mediated Silencing of Burkholderia O-Linked Glycosylation Systems Enables the Depletion of Glycosylation Yet Results in Modest Proteome Impacts

Abstract: The process of O-linked protein glycosylation is highly conserved across the Burkholderia genus and mediated by the oligosaccharyltransferase PglL. While our understanding of Burkholderia glycoproteomes has increased in recent years, little is known about how Burkholderia species respond to modulations in glycosylation. Utilizing CRISPR interference (CRISPRi), we explored the impact of silencing of O-linked glycosylation across four species of Burkholderia; Burkholderia cenocepacia K56-2, Burkholderia diffusa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 89 publications
(167 reference statements)
1
1
0
Order By: Relevance
“…Interestingly while previous studies have explored the impact of the abolishment of glycosylation, few studies have assessed how changes in glycosylation occupancy or glycosylation patterns impact bacterial proteomes. Recently it was demonstrated that within Burkholderia species the silencing of glycosylation using CRISPRi reduced occupancy but resulted in only modest proteomic impacts [84] yet in contrast our findings here support the N. gonorrhoeae proteome is extensively impacted by changes in glycosylation patterns. While O‐ linked glycosylation within B. cenocepacia has been shown to be important for the stability of multiple proteins [83, 85], we observed no change in the protein abundance of glycoproteins within this work suggesting that within N. gonorrhoeae O‐ linked glycosylation may exert its effects by modulating protein interactions or protein activities.…”
Section: Discussionsupporting
confidence: 56%
“…Interestingly while previous studies have explored the impact of the abolishment of glycosylation, few studies have assessed how changes in glycosylation occupancy or glycosylation patterns impact bacterial proteomes. Recently it was demonstrated that within Burkholderia species the silencing of glycosylation using CRISPRi reduced occupancy but resulted in only modest proteomic impacts [84] yet in contrast our findings here support the N. gonorrhoeae proteome is extensively impacted by changes in glycosylation patterns. While O‐ linked glycosylation within B. cenocepacia has been shown to be important for the stability of multiple proteins [83, 85], we observed no change in the protein abundance of glycoproteins within this work suggesting that within N. gonorrhoeae O‐ linked glycosylation may exert its effects by modulating protein interactions or protein activities.…”
Section: Discussionsupporting
confidence: 56%
“…By reducing the triggering of ETD/EThcD events to only potential glycopeptide precursors optimal ETD reaction times and/or extended ion filling times can be undertaken. However, while this approach has been widely utilized for the study of bacterial glycopeptides ,, we recently noted two examples within Moraxella osloensis and N. gonorrheae , wherein alterations within EThcD triggering was essential to allow site localization due to the lack of HexNAc residues within glycopeptides derived from these species. The diversity within the glycan structures utilized for O -linked glycosylation by A. baumannii strains supports the potential benefit of alternative ETD-triggering approaches to further improve glycoproteomic analysis of A. baumannii strains.…”
Section: Introductionmentioning
confidence: 99%